Bridging Biochemistry and Tumour Biology: LDH and CRP–Albumin Ratio in Relation to Ki-67 and Histological Aggressiveness of Breast Carcinoma - Abhinadan Greeg; Bora Sukesh (Journal of Medicine Pharmacology and Medical Devises Technology, 2026)
Background: Breast carcinoma exhibits considerable biological heterogeneity, and inexpensive circulating biomarkers capable of reflecting tumour aggressiveness may complement conventional pathological assessment. This study evaluated serum lactate dehydrogenase (LDH) and CRP–albumin ratio (CAR) in relation to histopathological features and Ki-67 proliferation. Methods: This prospective clinicopathological study included 128 treatment-naïve patients with primary breast carcinoma. Pretreatment serum LDH, CRP and albumin were measured, and CAR was calculated. Histological grade, lymphovascular invasion, nodal status, ER, PR, HER2 and Ki-67 were evaluated. Correlation, receiver-operating-characteristic analysis and multivariable logistic regression were performed. Results: Mean serum LDH increased significantly from 166.9±45.6 U/L in grade I to 286.2±48.1 U/L in grade III tumours (p